Association of resistome abundance with hyperuricaemia in elderly individuals: a metagenomics study - Liu, Zhiyang; Shen, Yingbo; Fu, Yulin; Sun, Da (Frontiers in Microbiomes, 2024)
IntroductionHyperuricaemia (HUA), one of chronic diseases, has an increased prevalence and is related to diseases such as gout, arthritis, infectious diseases, etc. Antimicrobial resistance (AMR) in the gut is considered as an atypical chronic disease, and poses risk to human health. The gut microbiome has been proved to be a reservoir for AMR and play an important role in HUA patients. The microbial characteristics of the gut in individuals with HUA have been previously explored, however, the characteristics of the resistome in individuals with HUA have remained largely unexplored.MethodsThus, we investigated the landscape of the AMR in individuals with HUA and without HUA, and the potentially influential factors in a case-control study using metagenomics-based approaches.ResultsWe found that drinking juice and abnormal stool were risk factors associated with HUA. The taxonomic diversity of gut microbiota in individuals with HUA was lower than that in non-HUA individuals. Notably, a higher abundance and diversity of the resistome (entire antimicrobial resistance genes) was observed in individuals with HUA (median: 1.10 vs. 0.76, P = 0.039, U-test), especially in tetracycline resistance genes (median: 0.46 vs. 0.20, P < 0.001, U-test), which are associated with more complex mobile genetic elements (MGEs) in individuals with HUA. Furthermore, we found that a higher abundance of the resistome was positively correlated with uric acid (UA) levels and affected by several host-associated factors (mainly dietary habits). Specifically, pork consumption and the consumption of root and tuber vegetables were identified as contributing factors. We also found a higher abundance of virulence genes (VGs), mostly related to adherence, antimicrobial activity, competitive advantage, and exoenzymes, in the gut microbial community of individuals with HUA.DiscussionAll findings revealed higher activity of the resistome and pathogenicity of the microbiota in individuals with HUA, indicating a higher health risk in the elderly HUA population.